Medical Maximizing-Minimizing Preferences Predict Responses to Information about Prostate-Specific Antigen Screening. (August 2018) - Scherer, Laura D.; Kullgren, Jeffrey T.; Caverly, Tanner; Scherer, Aaron M.; Shaffer, Victoria A.; Fagerlin, Angela; Zikmund-Fisher, Brian J.
Purpose: The recently developed Medical Maximizer-Minimizer Scale (MMS) assesses individual differences in preferences for active v. passive medical treatment. We hypothesized that men's maximizing-minimizing preferences might have relevance in the case of prostate-specific antigen (PSA) screening, since there is considerable variability in men's preference for being screened even among men who are informed that harm is more likely than benefit. The current research examined whether MMS preferences predict how men respond to didactic information and narrative stories about PSA screening.Design: US men 40+ years old ( N = 1208) participated in an online survey. Men viewed information about PSA screening in 3 phases and provided their preference for screening after each phase. Phase 1 described what PSA screening is. Phase 2 added didactic information about screening risks and benefits. Phase 3 added narrative stories; men were randomized to receive stories about 1) physical harm, 2) emotional harm, 3) overdiagnosis, or 4) all 3 stories. Participants also completed the validated MMS.Results: After receiving basic information, 76.8% of men wanted PSA screening. After receiving information about risks and benefits, 54.8% wanted screening (a significant reduction, P < 0.001). Men who changed their preferences were significantly more likely to be minimizers than maximizers; most men with maximizing tendencies wanted screening after both the didactic information and narratives, whereas most men with minimizing tendencies did not want the test after receiving information.Conclusions: Men who prefer a more minimizing approach to medicine are more responsive to evidence supporting limiting or forgoing screening than men who prefer a maximizing approach.